EFFECT OF INTERNAL LIMITING MEMBRANE PEELING ON LONG-TERM VISUAL OUTCOMES FOR DIABETIC MACULAR EDEMA. Issue 7 (July 2015) - Kumagai, Kazuyuki; Hangai, Masanori; Ogino, Nobuchika; Larson, Eric
Abstract : Purpose: To evaluate the effect of internal limiting membrane (ILM) peeling on the long-term visual outcomes in eyes with diffuse, nontractional diabetic macular edema. Methods: One hundred and sixteen eyes of 58 patients with the same degree of diabetic macular edema in both eyes underwent pars plana vitrectomy with the creation of a posterior vitreous detachment in both eyes. Internal limiting membrane peeling was performed in one randomly selected eye (ILM-off group), and ILM peeling was not performed (ILM-on group) in the fellow eye. The postoperative follow-up period ranged from 12 months to 161 months (average, 80.4 months). Results: In the ILM-off group, the mean best-corrected visual acuity in logMAR units (Snellen equivalent) increased from 0.55 ± 0.31 (20/71) before surgery to 0.35 ± 0.35 (20/45) at 1 year ( P < 0.0001) and 0.46 ± 0.43 (20/59) at the final visit ( P = 0.058). In the ILM-on group, the mean best-corrected visual acuity increased from 0.55 ± 0.41 (20/71) before surgery to 0.43 ± 0.38 (20/54) at 1 year ( P = 0.010) and 0.44 ± 0.45 (20/56) at the final visit ( P = 0.043). The differences in the best-corrected visual acuity between the two groups were not significant at any time point. Conclusion: Pars plana vitrectomy with or without ILM peeling improves the long-term visual acuity of nontractional diabetic macular edema. Internal limiting membrane peeling does not affect the postoperative best-corrected visual acuity significantly. Abstract : Pars plana vitrectomy with or without internal limiting membrane peeling leads to a significant improvement in best-corrected visual acuity in eyes with diffuse, nontractional diabetic macular edema. The improvement was maintained for periods with a mean of 80.4 months. There were no significant differences in the improvement of visual acuity with or without internal limiting membrane peeling.